ITIL service transition - Rance, Stuart (TSO (The Stationery Office) NorwichGB, 2011)
Provides best practice guidance for the service transition stage of the ITIL service lifecycle. Aims to ensure that new, modified or retired services meet the expectations of the business as documented in the service strategy and service design stages of the lifecycle. Provides guidance for the development and improvement of capabilities for transitioning new and changed services into supported environments, including release planning, building, testing, evaluation and deployment. Considers service retirement and transfer of services between service providers.